Terms of trade and economic growth: an estimate of the threshold level of terms of trade for Malaysia - Duasa, Jarita (International Economic Society, 2011)

(untitled)
The present study attempts to examine the non-linear relationship between terms of trade growth and economic growth in Malaysia by estimating precise threshold levels of terms of trade growth in each trading sector. In methodology, it employs relatively new econometric methods for threshold estimation and inference to ensure the significance of a structural break in the model as proposed by Hansen (1996, 2000). The results show that only prices of export and import of mineral fuels, lubricants and related materials (SITC3) is significantly and negatively affect the economic growth of the country. There also exists threshold effects in the relationship with two thresholds are identified and tested. The finding is that the negative impact is very much larger when the terms of trade growth is below the threshold of -1.576% but lesser when the terms of trade growth is higher than 0.0018%.